Beauty of nature / Nur Aliaa Dayana Binti Zainuri - Zainuri, Nur Aliaa Dayana (College of Creative Arts, 2022)
I was introduced to the world of art as early as 11 years old. My artwork inspiration comes from the beauty of natural dyes and issues that surrounds the environment. Through my artworks, I try to create textile design pieces by combining dyes from natural plants. I developed my designs through seeing five different plants giving a variation of natural dyes and inspiration in my design. I love the characteristics and how colourful the natural dyes are when we use different mordant for each plant source. I believe a good combination of natural dyes can pay tribute to mother nature that serves as a reminder for us to reconnect again with our natural environment.